Ektoparazitske trematode na vrsti Scardinius erythrophthalmus iz donjeg toka rijeke Save (VETERINARIA, 2020)
The research on ectoparasitic trematodes on Scardinius erythrophthalmus from the lower flow of the Sava River showed three species of trematodes, which parasitized on the fish gills and fish skin. During the study period, we sampled 120 individuals of Scardinius erythrophthalmus. In total, 85 individuals or more than 70% showed the presence of one of the three types of ectoparasitic trematodes. Determination of the trematodes was done to the species level for one species (Posthodiplosomum cuticola) and to the genus level for two of them (Dactylogyrus and Gyrodactylus).
Keywords: Sava River; lower flow; Orašje; ectoparasitic trematodes